2013
DOI: 10.1007/s13361-013-0585-1
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Phase Fragmentation of Oligoproline Peptide Ions Lacking Easily Mobilizable Protons

Abstract: The fragmentation of peptides containing quaternary ammonium group, but lacking easily mobilizable protons, was examined with the aid of deuterium-labeled analogs and quantum-chemical modeling. The fragmentation of oligoproline containing quaternary ammonium group involves the mobilization of hydrogens localized at α- and γ- or δ-carbon atoms in the pyrrolidine ring of proline. The study of the dissociation pattern highlights the unusual proline residue behavior during MS/MS experiments of peptides.Electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…The product ion spectra are used to match theoretical spectra generated from databases of ‘in silico’ digests of proteins and translated DNA for peptide sequencing. However, current search engines only take a few general fragment ions into account when matching the spectra to a database, while the influences of many other factors such as charge state, charge carrier, structure, and size of a peptide, as well as some sequence‐specific fragment ions on fragmentation patterns are limited considered . As a result, only a small percentage of the peptide fragmentation spectra are correctly matched to peptide sequences .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The product ion spectra are used to match theoretical spectra generated from databases of ‘in silico’ digests of proteins and translated DNA for peptide sequencing. However, current search engines only take a few general fragment ions into account when matching the spectra to a database, while the influences of many other factors such as charge state, charge carrier, structure, and size of a peptide, as well as some sequence‐specific fragment ions on fragmentation patterns are limited considered . As a result, only a small percentage of the peptide fragmentation spectra are correctly matched to peptide sequences .…”
Section: Introductionmentioning
confidence: 99%
“…However, current search engines only take a few general fragment ions into account when matching the spectra to a database, while the influences of many other factors such as charge state, charge carrier, structure, and size of a peptide, as well as some sequence-specific fragment ions on fragmentation patterns are limited considered. [3][4][5][6][7][8][9][10] As a result, only a small percentage of the peptide fragmentation spectra are correctly matched to peptide sequences. [11] Such sequence-specific fragment ions can be used to increase the confidence of peptide identifications if their fragmentation rule is incorporated into peptide sequencing algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we developed an efficient and straightforward method of isotopic exchange of acidic α-C hydrogens in N,N,N-trialkylglycine residues in peptides and discussed the application of such deuterium-labeled quaternary ammonium salt analogs for quantitative analysis of peptides. [24] We also used peptides containing the α-C deuterated N,N,N-trialkylglycine residues to study the mechanisms of peptide fragmentation during CID experiments [25,26] as well as hydrogen scrambling in non-covalent complexes of peptides. [27] In this article, we present our research on sarcosine-containing peptides, concerning the base-catalyzed HDX of α-C protons in sarcosine residue and specific hydrogen scrambling in such peptides.…”
mentioning
confidence: 99%
“…This study suggested that the presence of the acidic N-H a bond was crucial for the formation of peptide-y-ions. Recently, Szewczuk and coworkers carried out a series of studies on the fragmentation pathways in N-substituted oligopeptides, including oligoproline and oligosarcosine, with a quaternary ammonium (QA) group tagged at the N-terminus [56,57]. These peptides did not contain backbone N-H groups.…”
Section: Fragmentation Mechanism: Y-ion Formationmentioning
confidence: 99%